Scrap and Build for Functional Neural Circuits: Spatiotemporal Regulation of Dendrite Degeneration and Regeneration in Neural Development and Disease - Furusawa, Kotaro; Emoto, Kazuo (Frontiers in Cellular Neuroscience, 2021)
Dendrites are cellular structures essential for integration of neuronal information. These elegant but complex structures are highly patterned across the nervous system, but vary tremendously in their size and fine architecture, each designed to best serve specific computations within their networks. Recent in vivo imaging studies reveal that development of mature dendrite arbors in many cases involves extensive remodeling achieved through a precisely orchestrated interplay of growth, degeneration, and regeneration of dendritic branches. Both degeneration and regeneration of dendritic branches involve precise spatiotemporal regulation for proper wiring of functional networks. In particular, dendrite degeneration must be targeted in a compartmentalized manner to avoid neuronal death. Dysregulation of these developmental processes, in particular dendrite degeneration, are associated with certain types of pathology, injury, and aging. In this article, we review recent progresses in our understanding of dendrite degeneration and regeneration, focusing on molecular and cellular mechanisms underlying spatiotemporal control of dendrite remodeling in neural development. We further discuss how developmental dendrite degeneration and regeneration are molecularly and functionally related to dendrite remodeling in pathology, disease, and aging.